Periphyton uptake and trophic transfer of coal fly‐ash–derived trace elements. (17th July 2017) - Scheibener, Shane A.; Rivera, Nelson A.; Hesterberg, Dean; Duckworth, Owen W.; Buchwalter, David B.
Abstract: To determine whether the bioavailability of trace elements derived from coal ash leachates varies with the geochemical conditions associated with their formation, we quantified periphyton bioaccumulation and subsequent trophic transfer to the mayfly Neocloeon triangulifer . Oxic ash incubations favored periphyton uptake of arsenic, selenium, strontium, and manganese, whereas anoxic incubations favored periphyton uptake of uranium. Mayfly enrichment was strongest for selenium, whereas biodilution was observed for strontium, uranium, and arsenic. Environ Toxicol Chem 2017;36:2991–2996. © 2017 SETAC